3. Fenomena Penyelundupan Timah Indonesia ke Luar Negeri - Hari Adi Akbar Wijayanto; Hermini Susiatiningsih; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2017)
Tin smuggling is a main problem in the tin mining sector in Indonesia during 2009-2014 even though there are various regulations governing these tin mining activities. This research was conducted to determine the cause of the illegal practices in the tin mining still exist until nowadays. By using an explanatory research, this research aims to explain what happened, how the tin smuggling occurred, and the effects of the tin minning polices towards society. The logic of this research was formed by the analysis from two perspectives which are interrelated: the theory of economic crimes with the neoclassical approach and compliance theory. From these perspectives, the authors found the weaknesses of the policies, such as; influences of the actor’s rationality, ambiguity and temporal limitations of the policies, and the counterproductive impact of the policies on socio-economic conditions of the society that ultimately affect the rampant practice of illegal mining and tin smuggling during 2009-2014 in Indonesia.